2021
DOI: 10.3892/ol.2021.12445
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Twist, Slug and Snail in esophageal squamous cell carcinoma and their prognostic significance

Abstract: Esophageal cancer is one of the most common types of malignancy worldwide. At present, surgical resection is the main treatment for esophageal cancer, but recurrence and distant metastasis are the main causes of mortality. The transcription factors Twist, Slug and Snail regulate epithelial-mesenchymal transition and thereby participate in tumor invasion and metastasis. The aim of the present study was to investigate the expression of Twist, Slug and Snail in esophageal squamous cell carcinoma (ESCC) and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…The baseline characteristics of the included studies are shown in Table 1 . Among all eligible studies, six studies were published in English[ 11 - 14 , 17 , 18 ], while five were published in Chinese[ 15 , 16 , 19 - 21 ]. All included studies examined the expression of Twist in esophageal cancer tissue with immunohistochemistry (IHC).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The baseline characteristics of the included studies are shown in Table 1 . Among all eligible studies, six studies were published in English[ 11 - 14 , 17 , 18 ], while five were published in Chinese[ 15 , 16 , 19 - 21 ]. All included studies examined the expression of Twist in esophageal cancer tissue with immunohistochemistry (IHC).…”
Section: Resultsmentioning
confidence: 99%
“…All included studies examined the expression of Twist in esophageal cancer tissue with immunohistochemistry (IHC). Two metrics for IHC staining were used in some studies[ 11 , 12 , 18 - 21 ]: The percentage of positively stained cells and the staining intensity. However, some studies[ 13 - 17 ] evaluated Twist expression using only one metric for IHC staining, which resulted in assessing the expression of Twist at various cutoff values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…found that Snail is an independent risk factor for the prognosis of patients with esophageal cancer. The combination of Snail and Twist can significantly affect the overall survival rate of patients with esophageal cancer ( 38 ). It has also been reported that Snail is involved in the regulation of radiosensitivity in esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was found that PDCD4 directly interacts with the basic helix-loop-helix (bHLH) transcription factor Twist ( 66 ), a protein which has been attributed to having a role in mesoderm formation, myogenesis, neurogenesis and neural crest cell migration and differentiation ( 67 ), as well as endowing stem cell characteristics in tumour cells and promoting EMT ( 68 ). Twist has increased expression in oesophageal squamous cell carcinomas ( 69 ), is associated with gastric cancer progression ( 70 ) and increased proliferation and invasion in CRC ( 71 ). PDCD4 binding to twist results in the down regulation of the Twist target, Y-Box binding protein 1 (TB-1) and consequently a reduction in cell growth ( 66 ).…”
Section: The Interactions Of Pdcd4mentioning
confidence: 99%